A hypothetical model of trans-acting R-loops-mediated promoter-enhancer interactions by Alu elements. (20th November 2021) - Bai, Xue; Li, Feifei; Zhang, Zhihua
Abstract: Enhancers modulate gene expression by interacting with promoters. Models of enhancer-promoter interactions (EPIs) in the literature involve the activity of many components, including transcription factors and nucleic acid. However, the role that sequence similarity plays in EPIs remains largely unexplored. Herein, we report that Alu-derived sequences dominate sequence similarity between enhancers and promoters. After rejecting alternative DNA:DNA and DNA:RNA triplex models, we propose that enhancer-associated RNAs (eRNAs) may directly contact their targeted promoters by forming trans -acting R-loops at those Alu sequences. We show how the characteristic distribution of functional genomic data, such as RNA-DNA proximate ligation reads, binding of transcription factors, and RNA-binding proteins, all align with the Alu sequences of EPIs. We also show that these aligned Alu sequences may be subject to the constraint of coevolution, further implying the functional significance of these R-loop hybrids. Finally, our results imply that eRNA and Alu elements associate in a manner previously unrecognized in EPIs and the evolution of gene regulation networks in mammals.